Temperature related distribution of Lucyfer typus (Crustacea: Decapoda) in the Gulf of California - Hendrickx, Michel E; Estrada-Navarrete, Flor D (Revista de Biología Tropical, 1994)
Specimens of the pelagic shrimp Lucifer typus H. Milne Edwards were captured during three cruises in the Gulf of California, Mexico. The distribution of this species is compared with data of water temperature obtained at the surface and 50 m depth. These data suggest that the penetration of L. typus in the Gulf of California is limited by both the surface 20-21oC and the 50 m depth 18-190C isotherms, although in the Northern Gulf, shallow water and high turbidity might ¡imit the occurrence of this oceanic species.